Flexibilização de projetos mediante a análise do perfil sociodemográfico do consumidor do mercado imobiliário - Canedo, Ninfa Regina de Melo (2013)
The way of dwell and live, faces huge transformations that have been changing the society and its relationship with space. In a dynamic and competitive market, understand the consumer’s needs becomes imperative to define the product. Flexible spaces are capable to get adapted to a larger number of users, with different necessities in distinct moments of their housing career. This study has the will of investigate and analyze the real state’s production of the market of Goiás and the project’s flexible, considering a joint analysis of its socio demographic attributes that characterize the consumer’s behavior. It is a descriptive research and the methodology used for obtain the data and results was divided in three stages. The first stage was the theoretical review of the pertinent subjects, setting a bibliographic search. The second part corresponds to getting the data at the same time as the documental research, divided in three parts, on brazilian consumer’s profile, witch source was the information from IBGE, data collected at ADEMI-GO and at the design offered by the Goiás’ real state. The third and last part refers to a case study, where was rated an enterprise that belongs to the statement with the biggest flexible potential, covering also space and users. The analysis came from the gathering of information of the construction company and its departments, with the search of modified unities and through interviews and questionnaires that are about family life cicle, satisfaction and home choice, housing mobility and changes made at the house. Was observed that the Brazilian profile had been changed also sociodemographic, reflecting on it’s way of residing. On the market of Goiás was observed the predominance of smaller apartments, with more selling on 2 and 3 bedrooms types, and estimated 50 to 90 m2 area, that represent together 80% of this segment. The market already practice flexible on the homes, being the most frequent modifications the ones referent to a neutral ambient between the sectors: the reversible room; the bathroom between two bedrooms, usable as a “suite”, the kitchen with a bigger wall shared with the living room, making the integration or separation possible. The size that gives the biggest possibility of flexible, in the areas proposed by the study are 120 to 150 m2. Can be concluded that the project’s flexible is indispensable by the building market consumer’s demand of the studied population, since it attends a larger number of users, even in the purchase, in adaptation to the individual needs or in reselling this one or another dweller profile.